Solve the following systems of initial-value problems using the Laplace transform method: x'' + y' = 5e-t , y'' - x = sint , x(0) = 1 , x'(0) = 0 , y(0) = -2 , y'(0) = 0

Solve the following systems of initial-value problems using the Laplace transform method: x'' + y' = 5e-t , y'' - x = sint , x(0) = 1 , x'(0) = 0 , y(0) = -2 , y'(0) = 0

Solve the following initial-value problem using Laplace transforms. y''- y' - 2y = 5sin(x) ; y(0) = 1 , y'(0) = -1

use laplace transform

Assuming B and F is a function of time, would it be possible to derive B(t) in the following equation where dB(t)/dt + cB(t) = F(t) possibly using laplace transform?

Laplace [1/t * e^-1/t]

Solve By using laplace transform and its application

how to deduce that lims=0 s u(s) = limt=infinite U(t) sorry the equal sign (subscript) should be replaced with an arrow which indicates "approaching", I couldn't...

Use Laplace Transform to solve the following Problem Engineering system can either be in three states: i = 0 (operating normally), i = 1 (failed due to hardware problem), i=2 (failed...

How to solve the following equations by using Laplace Transform? 1) x' + x - y = 1 + sint 2) y' - x' + y = t - sint Given: x(0)=0,y(0)=1

How do i find laplace transform the equation

There was a question on my homework today: Work out the formula for the Laplace operator in polar coordinates. How do I do with this question?

given in series circuit L=1H, R=110ohm, C=0.001F, v=90V. Find the resultant current when the switch is originally open and it is closed for 1s. then it is open again when t=1. use laplace transform...

Hi i need to know how to use the Laplace Transform, to resolve f(t)=t^n*e^a*t. very thanks!

Use the Laplace transform to solve y^(4)-4y'''+6y"-4y'+y=0; y(0)=0, y'(0)=1, y"(0)=0, y'''(0)=1. Answer: y=te^t-t^2*e^t+(2/3)t^3*e^t L(y^(4))-4L(y''')+6L(y")-4L(y')+L(y)=L(0) But...

Use the Laplace transform to solve y"-y'-6y=0; y(0)=1, y'(0)=-1. Answer: y=(1/5)(e^(3t)+4e^(-2t)) I don't know how to take the Laplace transform for both sides. Help me step by step...

Find the inverse Laplace transform of F(s)=G(s)/(s^2+1) by using the convolution theorem.